2018
DOI: 10.1186/s13049-018-0570-6
|View full text |Cite
|
Sign up to set email alerts
|

ECMO improves survival following cardiogenic shock due to carbon monoxide poisoning - an experimental porcine model

Abstract: BackgroundSevere intoxication with carbon monoxide (CO) is extremely lethal and causes numerous deaths due to cardiac or respiratory failure. Conventional intensive treatment may not be sufficient. The aim of this study was to investigate the treatment effect of extracorporeal veno-arterial extracorporeal membrane oxygenation (ECMO) following severe CO poisoning in an experimental porcine model.MethodsA total of twelve pigs were anaesthetized, routinely monitored and intoxicated by inhalation of CO until the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Ventricular brillation is the most frequent side-effect of previous experimental cardiogenic shock models, leading to death in up to 50% of animals [16,17,21,27]. To reduce the loss of animals, antiarrhythmics were administered before ethanol injection, and this resulted in ventricular brillation in only one animal.…”
Section: Con Rming Site-speci C Injury: Electrophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Ventricular brillation is the most frequent side-effect of previous experimental cardiogenic shock models, leading to death in up to 50% of animals [16,17,21,27]. To reduce the loss of animals, antiarrhythmics were administered before ethanol injection, and this resulted in ventricular brillation in only one animal.…”
Section: Con Rming Site-speci C Injury: Electrophysiologymentioning
confidence: 99%
“…In particular, reproducing a stable cardiogenic shock model by ligating major coronary arteries often resulted in refractory and lifethreatening ventricular arrhythmias [16][17][18][19]. Other methods, such as carbon monoxide poisoning or druginduced CS (beta-blockers), have resulted in heterogeneous outcomes and cause a global decrease in ventricular contractility, different to regional wall motion abnormalities usually seen in myocardial infarction [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…First, systemic or selective coronary hypoxemia 5 is responsible for a generalized diminished cardiac function due to the hibernating myocardial condition: in this setting, cellular mechanisms of adaptation are not the same than in distinct infarcted myocardium. Similar concerns should be taken into account in the case of global toxicity, induced by carbon monoxide 6 . The use of microspheres could overcome this difficulty 7 , but the injection in the left main coronary artery has a generalized effect on the left ventricle and is associated with a jeopardized cellular death in the whole myocardial wall thickness.…”
Section: Introductionmentioning
confidence: 99%
“…The use of microspheres could overcome this difficulty 7 , but the injection in the left main coronary artery has a generalized effect on the left ventricle and is associated with a jeopardized cellular death in the whole myocardial wall thickness. Furthermore, the set-up of several studies requires STMCS activation soon after 6 , 7 or even before 8 CS induction in order to avoid premature death of animals, or an open-chest procedure for coronary ligatures 9 , which completely modifies the heart-pericardium and heart–lung interactions. In recent studies suggesting that early mechanical percutaneous support prior to revascularization might reduce the size of myocardial necrosis 10 , a condition of mild systemic hypo-perfusion is obtained rather than an effective hemodynamic CS.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the lack of efficacy basis, the application of hyperbaric oxygen to ACOP patients still lacks relevant evidence (7). In recent years, due to the development of extracorporeal circulation technology, extracorporeal membrane oxygenation (ECMO) technology has been gradually applied to the treatment of ACOP, and Simonsen et al (8) reported that ECMO treatment can improve the survival rate of ACOP patients with cardiogenic shock, but its exact efficacy is currently less studied.…”
Section: Introductionmentioning
confidence: 99%